Pergeseran Paradigma Tafsir Islamis di Indonesia (Studi Kasus Mohammad Natsir dan Felix Y Siauw) - Ilmi, Robby Hidayatul; Fauzi, Ahmad (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Islamists have always been defined by two categories, politically they want to unite religion and state and religiously they are literalists. This article will re-examine these two theses by assuming that not all islamists are literalists. Using descriptive-analytical method, this article will compare the interpretation of two prominent islamists leaders, Mohammad Natsir (early Islamist) and Felix Y Siauw (contemporary Islamist). Hans-Georg Gadamer's hermeneutics will be used as an analytical method whereas Abdul Mustaqim's epistemological classification of tafsiir will be used to map those islamist thoughts among other scholars. This article found, firstly, that not all islamists understand the Qur'an literally. Islamists are the same as literalists was produced by research that take sample on post-Soeharto Islamists. Second, there is a shift in the paradigm of islamists interpretation. The early phase of Islamists tended to be more contextual and influenced by early islamic reform. As for contemporary Islamists, they tend to be textual and militant. This research has shown that it is necessary to study these islamists, especially their understanding of Qur’anic text.